Reference Levels of Plasma D-dimer for Normal Pregnant and Their Association with Pregnancy Complications: A Single-center Retrospective Analysis - Wang, Wenhuan; Dai, Qiqi; Pan, Liqin; Zhang, Hongping; Wang, Yeping (Clinical and experimental obstetrics & gynecology, 2024)
Background: The objective of this study was to extract maternal plasma D-dimer test results from a large medical records dataset and to establish a reference level for pregnant women in our center. This study aimed to investigate the role and efficacy of D-dimer levels for predicting complications in high-risk pregnant women. Methods: The clinical data of 19,117 women who delivered at Wenzhou People’s Hospital between January 1, 2020, and September 30, 2022, were retrospectively analyzed. A total of 74,401 D-dimer test results were extracted from the laboratory information system. Following data screening and matching, 7692 records of D-dimer test results for healthy pregnant women and 19,005 records for pregnant women with complications were selected. D-dimer reference values were calculated for early pregnancy (1–13 weeks gestation), mid-pregnancy (14–27 weeks gestation), late pregnancy (28–36 weeks gestation), and the end of pregnancy (37–41 weeks gestation). A logistic regression model was used to plot receiver operating characteristic (ROC) and determine cut-off values for predicting pregnancy complications in each phase. Results: The mean D-dimer levels in the healthy pregnancy group were 0.56 mg/L in early pregnancy, 1.08 mg/L in mid-pregnancy, 1.48 mg/L in late pregnancy, and 1.89 mg/L at the end of pregnancy. D-dimer levels were greater in the complication group (which contains 11 common pregnancy disorders, including premature rupture of membranes (PRM), gestational diabetes mellitus (GDM), gestational hypertension (GHP), preeclampsia (PE), placental abnormalities, thyroid dysfunction, hemorrhage, thrombophilia, fetal macrosomia, preterm delivery, and infections) than in the healthy group in all pregnancy phases, with statistically significant differences observed in early, medium, and the end of pregnancy. D-dimer levels showed good diagnostic performance in predicting pregnancy complications in early pregnancy (area under the curve (AUC) = 0.71, cut-off value = 0.87, odds ratio: 7.12, 95% confidence interval (CI): 5.41–9.36, p-value = 0.000). Conclusions: The reference range of D-dimer increases with the progression of gestational phases and demonstrates predictive efficacy for high-risk pregnancy complications during early pregnancy.